The rise of China and India: blessing or curse for the advanced countries? - Livio Stracca (European Central Bank (ECB), 2013)
This paper evaluates the impact of the rise of large emerging manufacturing exporters such as China and India on economic growth in advanced countries. After illustrating the possible theoretical channels, I estimate a growth regression based on 3-year average data augmented with country-specific measures of import and export competition from China and India using instrumental variables. Stronger import competition from China and India leads to stronger income growth in advanced countries, but to a loss of manufacturing jobs. A more flexible labour market, lower concentration of employment in manufacturing and pre-existing trade links with China and India help advanced countries to maximise the growth dividend resulting from their rise in world export markets.
Keywords: F02; F15; 330; China; comparative advantage; economic growth; globalisation; India; offshoring; trade